PENGARUH LAMA PENGADUKAN DAN KONSENTRASI STPP TERHADAP KARAKTERISTIK PATI SUWEG (Amorphophallus campanulatus) TERMODIFIKASI IKATAN SILANG - Setiyoko, Agus; Yuliani, Fety Andrianing (Jurnal Teknologi Hasil Pertanian, 2021)
This study aimed to find out the effect of the combination of Sodium Tripolyphosphate (STPP) and stirring time on physical and chemical characteristics of the produced suweg starch. A factorial completely randomized design (CRD) was used in this study.  The study was conducted using 2 treatment factors, namely the addition of Sodium Tripolyphosphate (STPP) concentrations in 1% and 2% level and stirring time for 30 minutes and 60 minutes. The research method use 2 factorial Randomized Block Design (RBD). The data obtained was performed by ANOVA statistical tests and if the result significantly different it would be followed by the Duncan Multiple Range Test at a 5% confidence level. The results showed the effect of the combination of Sodium Tripolyphosphate (STPP) and stirring time on the physical and chemical characteristics of the resulting suweg starch compared to the control suweg starch in the form of an increase in the value of brightness, amylopectin content and solubility, while the value of redness (a*), yellowness (b*), water content, amylose content, and swelling power decreased